REGULATION OF AUXIN COMPOUND IN IN VITRO CULTURE OF GO POTATO SEEDS PRODUCTION - Misbah Ruhiyat; Syarif Husen; Nurina Farahiyah (UPT Penerbitan Universitas Jember, 2017)
Auxin has a role in the growth and development of plant roots. This research examinedthe effect of IAA and NAA growth regulators in in vitro culture of potato. Employing grouprandomized design, this research was conducted in